Corporate governance, firm financial performance and shareholders’ confidence: A proposed analysis of MCCG 2012 - Rahman, Haseeb Ur; Ibrahim, Mohd Yussoff; Che Ahmad, Ayoib (Universal Publishers, 2015)
Purpose: It is a common belief that an independent board improves firm financial performance and shareholders’ confidence.The separate leadership structure and independent chair of the board are considered to strengthen independence of the board. This paper, therefore, proposes to investigate that how Malaysian Code on Corporate Governance (MCCG 2012) impacted board independence (separate leadership structure and independent chair) and its relation with firm performance and shareholders’confidence. Design/Methodology/Approach: The proposed model of the paper based on agency theory and MCCG 2012, recommends to investigate that how MCCG 2012 impacted shareholders’ confidence with a mediation of firm performance in pre and post context of the code from 2010-2013.The proposed data regarding corporate governance will be collected from annual reports while firm financial performance (ROE & EPS) and shareholders’ confidence (share price) from DATA STREAM for a sample of 300 Malaysian listed companies.Findings: The MCCG 2012 anticipated that independence of the board will improve firm performance and shareholders’ confidence. However, these anticipations yet lack empirical support. Thus, this paper proposes to find empirical evidence and fills the literature gap.Practical Implications: The proposed study will provide empirical evidence that how the code (separate leadership structure and independent chairman) impacted its level of compliance, firm performance and shareholders’ confidence which will have value for Bursa Malaysia, Securities Commission, shareholders and management of the companies in Malaysia.Originality/Value: The limited literature regarding CG codes in pre and post context has been investigated in relation to firm performance.This paper proposes to investigate the mediation role of firm performance between MCCG 2012 and shareholders’ confidence which has never been investigated earlier.Moreover, the proposed study will be the first study related to MCCG 2012 as the previous literature is regarding other codes in Malaysia or outside.